Serial Mediated Effects of Emotional Intelligence and Quality of Work Life as Mediators Transferring Psychological Capital towards Job Performance of Thai Tour Guides - Pakdeeagsorn, Chote; Boonyoo, Thanyanan; Ramanust, Sumalee (Rajapark Journal, 2023)
The objectives in this study were to explore emotional intelligence and quality of work life as a serial mediated variables transferring psychological capital towards job performance of Thai tour guides. For quantitative research, this study investigated general Thai tour guides who served both Thai and foreign tourists. The participants in this research were 500 tour guides, who had already obtained the tour guide licenses. Statistics used to analyze in this study consisted of frequency, percentage, means, standard deviation (SD), coefficient of variation, and path analysis by ADANCO 2.2.1 program. Results of influences of serial mediated effects of emotional intelligence and quality of work life as serial mediated factors transferring influences of psychological capital towards job performance of Thai tour guides could be concluded that the coefficient variation of multiplied path analysis of emotional intelligence and quality of work life are regarded as a serial mediated effects transferring psychological capital and quality of work life of Thai tour guides.